2017
DOI: 10.1136/bmjopen-2016-015549
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder: updated prevalence and comparison of two birth cohorts in a nationally representative Australian sample

Abstract: ObjectivesThis study aimed to (1) provide an update on the prevalence of parent-reported autism spectrum disorder (ASD) diagnosis and new information about teacher-reported ASD in two nationally representative Australian cohorts at ages 10–11 years, (2) examine differences in cohort demographic and clinical profiles and (3) compare the prevalence of teacher-reported ASD and any changes in categorisation over time across the cohorts.DesignSecondary analyses were undertaken using data from the Longitudinal Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 20 publications
4
64
0
1
Order By: Relevance
“…Fifteen percent of our sample were reported to have a child with either ADHD or ASD. Given that these conditions are associated with increased child and parent mental health symptoms (Craig et al, 2016;Efron et al, 2014;Skokauskas & Gallagher, 2012), and that these rates appear higher than other Australian population estimates (Efron et al, 2020;May, Sciberras, Brignell, & Williams, 2017), we conducted sensitivity analyses excluding children with ADHD or ASD from the sample.…”
Section: Pre-existing and Covid-19 Related Risk Factorsmentioning
confidence: 99%
“…Fifteen percent of our sample were reported to have a child with either ADHD or ASD. Given that these conditions are associated with increased child and parent mental health symptoms (Craig et al, 2016;Efron et al, 2014;Skokauskas & Gallagher, 2012), and that these rates appear higher than other Australian population estimates (Efron et al, 2020;May, Sciberras, Brignell, & Williams, 2017), we conducted sensitivity analyses excluding children with ADHD or ASD from the sample.…”
Section: Pre-existing and Covid-19 Related Risk Factorsmentioning
confidence: 99%
“…The prevalence of ASD is reported as approximately one per cent in UK populations . Recently, Christensen et al, in a large‐scale study in the USA, reported a higher prevalence of one in 68 children (1.5 per cent), and May et al found a 2.4 per cent parent‐reported prevalence in a nationally representative sample of children in Australia born in 1999/2000. Indeed, the past 20 years have seen a significant shift in the awareness of autism and demands on community services and interventions.…”
Section: Prevalencementioning
confidence: 99%
“…A real increase in ASD cannot be excluded even though it might be explained by improvements in documentation and the diagnosis of milder cases. 2,3 The pathophysiology of the disease is not well understood but multifactorial etiology is suggested by the current evidence. 1 Various genetic and environmental factors have been found to be associated with ASD, including, advanced paternal age and exposure to heavy metals such as lead and inorganic mercury.…”
mentioning
confidence: 99%